2014
DOI: 10.1155/2014/153981
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G Dimers in the Prolongation of Kidney Allograft Survival

Abstract: Human leukocyte antigen-G (HLA-G) contributes to acceptance of allografts in solid organ/tissue transplantation. Most studies have determined that soluble HLA-G isoforms are systematically detected in serum/plasma of transplanted patients with significantly fewer episodes of acute and/or chronic rejection of allogeneic tissue/organ. Current models of the interactions of HLA-G and its specific receptors explain it as functioning in a monomeric form. However, in recent years, new data has revealed the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
0
18
1
Order By: Relevance
“…Many studies observed that higher serum HLA-G level or HLA-G mRNA expression is associated with kidney graft acceptance [8,18,[20][21][22][23]26,31]. The authors have suggested that soluble HLA-G could be used as additional marker to monitor the graft acceptance outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies observed that higher serum HLA-G level or HLA-G mRNA expression is associated with kidney graft acceptance [8,18,[20][21][22][23]26,31]. The authors have suggested that soluble HLA-G could be used as additional marker to monitor the graft acceptance outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In kidney transplant patients, increased soluble HLA-G level was significantly associated with better graft acceptance [8,18,[20][21][22][23]. As the expression of sHLA-G may be influenced by the 14 bp insertion polymorphism [15], the possible association between this variant and graft acceptance has been investigated, but the results are controversial.…”
Section: Genotyping Of Hla-g 14 Bp Polymorphism At Exon 8 (3´ Utr)mentioning
confidence: 99%
“…In this study, the investigators evaluated the levels of sHLA-G1 and HLA-G5 dimers and monomer isoforms. In confirmation of their finding, the increased cellsurface expression of HLA-G on monocytes of patients with no rejection episodes was found to be associated with high levels of plasma sHLA-G dimers [100]. These observations underscore the potential of HLA-G in graft acceptance; but it remains to be determined whether this potential is due to cell-surface expression of HLA-G1 or whether its soluble form, HLA-G5, induces graft acceptance in the course of its specific mechanism of action.…”
Section: Immunobiology Of Soluble Hla-ib In Transplantationmentioning
confidence: 54%
“…Indeed the recent article published 2014, addressing the role of HLA-G dimers in the prolongation of kidney allograft survival supports this concept. 16 …”
Section: Discussionmentioning
confidence: 99%